English vocabulary learning among the School of International Hospitality and Tourism Management students - Dapiawen, Aida A. (University of Baguio Sukimat, 2015)
This study sought to describe the vocabulary learning techniques among the students of the School of International Hospitality and Tourism Management. A questionnaire-checklist was utilized to gather needed data. The participants in the study were the Bachelor of Science in Hotel and Restaurant Management (BSHRM), the Bachelor of Science in Tourism Management (BSTM), and the Associate in Hotel and Restaurant Management students enrolled in English 1 for 1st semester of the A.Y.2014-2015. The sample size of 488 participants were randomly picked from the different sections of the three courses. Frequency counts and weighted mean were used to get the data on the students' frequency of using vocabulary learning techniques, and their degree of agreement on the perceived benefits of having a wide or rich vocabulary. The findings reveal that the students rarely use the vocabulary learning techniques, but they strongly agree on the perceived benefits of an enhanced vocabulary.